Perlindungan Hukum Seni Batik Karawang Ditinjau Melalui Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Munirotul Qolbiyah; Devi Siti Hamzah Marpaung (Ajudikasi : Jurnal Ilmu Hukum, 2020)
This writing aims to find out how the development of batik in Karawang Regency as well as legal protection of the batik copyright typical of Karawang Regency with the provisions contained in Law Number 28 of 2014 concerning Copyright. Batik art is a technique of drawing on cloth and utilizing wax and canting as materials and tools to make it, batik is one of the works of art that requires high intellectuality in its creation. Legal protection of batik copyright is needed to avoid things that will be detrimental to the creator and copyright holder. The approach method used in this research is juridical empirical, which is research based on legislation and also using research based on facts, realities and problems in the field. The empirical juridical approach is a study that examines legal regulations, namely Law Number 28 of 2014 concerning Copyright, which is then linked with data from research research on batik typical of Karawang Regency. Keywords: Protection; Copyright; Batik; Art.